Uncertainty spillovers from advanced, emerging, and low-income economies and firm-level stock returns in Vietnam: Does state ownership matter? - Thanh Huu Phu Nguyen; Ho Hoang Gia Bao; Hoang Phong Le; Ba Hoang Nguyen (Journal of Open Innovation: Technology, Market and Complexity)
This study analyzes the spillover effects of economic and political uncertainty from advanced, emerging and low-income economies on stock returns in Vietnam based on a firm-level approach. After controlling for firm-level and country-level factors and addressing potential endogeneity issues, we find positive associations between uncertainties in advanced, emerging and low-income markets and stock returns in Vietnam. However, the positive spillover effects from advanced and emerging markets become weaker for state-owned organizations. The findings remain robust across different econometric specifications. The study, therefore, offers novel empirical evidence from an emerging market together with several practical implications for policymakers and investors.